From Reference to Sense: How the Brain Encodes Meaning for Speaking - Menenti, Laura; Petersson, Karl Magnus; Hagoort, Peter (Frontiers in Psychology, 2012)
In speaking, semantic encoding is the conversion of a nonverbal mental representation (the reference) into a semantic structure suitable for expression (the sense). In this fMRI study on sentence production we investigate how the speaking brain accomplishes this transition from nonverbal to verbal representations. In an overt picture description task, we manipulated repetition of sense (the semantic structure of the sentence) and reference (the described situation) separately. By investigating brain areas showing response adaptation to repetition of each of these sentence properties, we disentangle the neuronal infrastructure for these two components of semantic encoding. We also performed a control experiment with the same stimuli and design but without any linguistic task to identify areas involved in perception of the stimuli per se. The bilateral inferior parietal lobes were selectively sensitive to repetition of reference, while left inferior frontal gyrus showed selective suppression to repetition of sense. Strikingly, a widespread network of areas associated with language processing (left middle frontal gyrus, bilateral superior parietal lobes and bilateral posterior temporal gyri) all showed repetition suppression to both sense and reference processing. These areas are probably involved in mapping reference onto sense, the crucial step in semantic encoding. These results enable us to track the transition from nonverbal to verbal representations in our brains.